A sustainable nanocomposite, graphene oxide bi-functionalized with chitosan and magnetic nanoparticles for enhanced removal of Sudan dyes. Issue 5 (19th April 2023) - Khawaja, Heena; Zahir, Erum; Asghar, Muhammad Asif; Asghar, Muhammad Arif; Daniel, Asher Benjamin
Abstract: The environmental pollution, particularly water pollution, has gradually caused severe human health issues. Organic dyes are one of the most emerging pollutants in the environment. In the present study, graphene oxide (GO) was functionalized with chitosan (CS) and magnetic nanoparticles (Fe-NPs) and tested to remove Sudan I, II, III, and IV dyes from water. The synthesized GO-CS-Fe was characterized using UV–vis, SEM, TEM, EDX, and FTIR spectroscopy, and confirmed the structural composition of nanocomposite, with the Fe-NPs dimension over the GO-CS surface to be 31–44 nm. The effects of various experimental factors; time, pH, adsorbent amount, dyes concentrations, and temperature were executed using the batch experiment. The experimental data were fitted to pseudo-first-order, pseudo-second-order, intraparticle diffusion, and Elovich kinetic models. The isotherm models parameters of the Langmuir, Freundlich, Redlich–Peterson, Temkin, and Hill isotherms, along with the thermodynamics parameters were also calculated. The data was explained by the Langmuir isotherm model with maximum adsorption capacities for Sudan I, II, III, and IV as 360.6, 353.7, 351.0, and 347.6 mg/g, respectively. The rapid uptake of the dyes fitted the pseudo-second-order kinetic, asserting that the adsorption was diffusion controlled. The process was spontaneous and endothermic in nature. The reusability study of GO-CS-Fe was performed up to five cycles. The nanocomposite can retain its efficacy even after the considered cycles. In conclusion, the GO-CS-Fe nanocomposite has exhibited a high potential for removing Sudan dyes from the aqueous solution due to its high adsorption and regeneration capability. Graphical Abstract: UF0001